BIAS GENDER DALAM KOMUNIKASI DI LINGKUNGAN PESANTREN - Sumadi Sumadi (Indonesian Journal of Dialectics, 2011)
One of the discourse of modernization ideas that rejected in Pesantren Miftahul Huda is gender. At least there are four problems related to gender in communication in pesantren, namely: (a) the source of ideological discourse of gender bias, (b) agents of ideology of gender bias, (c) communication that is gender bias, (d) and gender inequality. To explain the issue a critical ethnographic approach was used through the theory of ideology (deep unconsciousness), the theory of communication performance (performance), and feminist theory. The research findings indicate the occurrence of gender bias in communication in The Pesantren of Miftahul Huda in various aspects.